Gonadal maturation stages of the oceanic paddler crab, Varuna litterata (Fabricius, 1798) from Brgy. Mojon, Belison, Antique, Philippines - Trocho, Edlyn L.
The gonadal maturation stages of the oceanic paddler crab, Varuna litterata (Fabricius, 1798) from Brgy. Mojon, Belison, Antique, Philippines were determined through macroscopic and microscopic technique. This information will provide baseline information on the reproductive biology of the V. litterata and will be valuable for the broodstock management in the hatchery. The collected samples were examined based on their external morphology and histological appearance. The results revealed four stages for females, three stages for males and two stages for the ?bakla? category. The female stages were (1) immature ? white with presence of small oocytes, oogonia, and follicle cells, (2) early maturing ? yellow, larger oocytes, smaller nucleus, (3) late maturing ? orange, appearance of yolk globules and (4) fully mature with three substages (4.1) light brown, large yolk globules in cytoplasm, (4.2) reddish brown, increased size of yolk globules and (4.3) dark brown, larger yolk globules than earlier stages, decrease in size of nucleus. The male stages were (1) immature ? barely visible to translucent, presence of spermatogonia and spermatocytes (2) maturing ? white, presence of spermatocytes and spermatids and (3) mature ? milky white, presence of spermatozoids. The ?bakla? stages were (1) immature ? barely visible to translucent, small oocytes with large nuclei and (2) mature ? white, presence of oocytes and follicle cells at the periphery, proving that ?bakla? is an immature female.